Petrografia e microestruturas do anortosito carreira comprida - Porto Nacional, TO - PONTES, Gabriel Silva de Araújo (2020)
This paper presents the petrographic and microstructural data of the Carreira Comprida Anorthosite, into the Porto Nacional - Brejinho de Nazaré region (TO), on the northern portion of the Tocantins Province, into the Goiás Massif, between the Araguaia and Brasilia belts. This paper aim is to identify the metamorphism effects into this anortositic body, and to describe the mineralogical, textural and microstructural transformations in the pluton, aiming to identify the metamorphic conditions and the structural/microstructural transformations due to the deformation’s effects caused by the shearing thought the Transbrasiliano Lineament. At first, it was made a survey of all cartographic and bibliographic content concerning the geological knowledge of the Tocantins Province, the Porto Nacional high-grade metamorphic terrain and the Carreira Comprida Anorthosite. Then, the fieldwork phase had been done to collect representative samples of the unit for petrographic studies. From the petrographic and microstructural data obtained, it was possible to divide the anorthosite into three distinct petrographic types according their paragenesis and dominant microstructural features in each domain: a) Anorthosites with preserved magmatic features (Plg + Cpx + Ilm); b) meta anorthosites (Plg + Cpx + Hbl + Bt + Grt + Ttn); and c) mylonitic anorthosites (Plg + Hbl + Bt + Grt + Ttn). The presence of a metamorphic mineral assemblage defines the Carreira Comprida Anorthosite as a meta-anorthosite. The obtained mineral associations reveal amphibolite facies metamorphism, with temperatures ranging between 600 and 700ºC at medium to high pressure conditions. The petrographic domain marked by “a)” has well preserved magmatic features, without hornblende and biotite in its composition, demonstrating lower metamorphic conditions for this petrographic type. The microstructural analysis pointed the presence of microtextures caused by deformation under ductile conditions. The obtained data interpretation data indicates the variation into the meta-anorthosite’s metamorphic conditions and deformation grades, with more intense deformation occurring in the mylonitic anorthosites located in the eastern portion of the pluton, affected by the Porto Nacional Shear Zone.